2004
DOI: 10.1111/j.1365-2842.2004.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of acrylic resins submitted to mechanical and chemical polishing

Abstract: Surface roughness is extremely important as it influences micro-organism accumulation and consequently oral health. The aim of the present study was to evaluate the influence of mechanical polishing (MP) and chemical polishing (CP) on surface roughness of four heat-cured denture base acrylic resins. Twenty sample discs were prepared for each of the following acrylic resins: Classico (CL), QC 20 (QC), Acron MC (AC) and Onda Cryl (ON). The first two are boiling cured resins and the latter two are microwave cured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 11 publications
(14 reference statements)
6
55
0
14
Order By: Relevance
“…Polishing techniques indeed influenced the Ra; mechanical polishing was superior to chemical polishing in this aspect (Table 2), as only the first one achieved surface roughness under 2.0 m, which is the value previously established as a threshold for surface roughness in these cases. 7 This is in accordance with Rahal et al, 8 who also found that the chemical polishing generated rougher surfaces than mechanical polishing. Zissis et al 9 did not polish the tested surfaces and found surface roughness between 3.4 and 7.6 m, higher than the values found in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Polishing techniques indeed influenced the Ra; mechanical polishing was superior to chemical polishing in this aspect (Table 2), as only the first one achieved surface roughness under 2.0 m, which is the value previously established as a threshold for surface roughness in these cases. 7 This is in accordance with Rahal et al, 8 who also found that the chemical polishing generated rougher surfaces than mechanical polishing. Zissis et al 9 did not polish the tested surfaces and found surface roughness between 3.4 and 7.6 m, higher than the values found in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, few of the most commonly used disinfectants such as sodium hypochlorite; glutaraldehyde, chlorhexidine and sodium perborate [3,[15][16][17][25][26][27][28][29] were used in present study. The micro-organisms namely Streptococcus mutans and Candida albicans were studied since they are common commensals of oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Studies done on various disinfectants, have shown that sodium perborate can be substituted with more effective disinfectants like sodium hypochlorite [3,[15][16][17][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The surface roughness calculated between 0.5 and 10 µm is rough enough to retain the bacterial plaque and is clinically not acceptable. 25 Low pH results in loss of minerals adsorbed on the dental hard tissues, thus affecting the surface. 26,27 Surface roughness Ra parameter increases with time in different tested energy beverages, and it was highly significantly different in all glass ionomer restorative materials immersed with Code Red (p = 0.000), Red Bull (p = 0.000), and Power Horse (p = 0.000); the surface roughness values were measured using surface scanning interferometry.…”
Section: Discussionmentioning
confidence: 99%